Propensity score regression analysis of oesophageal adenocarcinoma treatment with surgery alone or neoadjuvant chemotherapy. Issue 4 (6th May 2020) - Powell, A G M T; Karran, A; Blake, P; Christian, A; Roberts, S A; Lewis, W G
Abstract: Background: Propensity score (PS) regression analysis can be used to minimize differences between cohorts in order to perform comparisons The aim of this study was to use PS analysis to examine the outcomes of oesophageal adenocarcinoma (OAC) treatment with surgery alone or neoadjuvant chemotherapy (NAC) followed by surgery (NACS), to see whether the benefits seen in a randomized trial (MRC OE02) were reproducible in a UK cancer network clinical practice. Methods: Consecutive patients undergoing potentially curative treatment for OAC in a regional cancer network were studied. Multiple regression models, including PS analysis, were developed to account for confounding factors. Primary outcome measures were disease-free (DFS) and overall (OS) survival. Results: A cohort of 440 patients was included in a regression analysis controlling for confounders (176 surgery alone, 264 NACS). NACS was associated with a higher positive margin status rate compared with surgery alone (42·4 versus 26·7 per cent respectively; P < 0·001), an inferior 5-year DFS rate (32·1 versus 56·9 per cent; P < 0·001) and a worse 5-year OS rate (27·5 versus 47·3 per cent; P < 0·001). On regression adjustment based on propensity scores, NACS was not associated with DFS ( P = 0·220) or OS ( P = 0·431). The Mandard tumour regression grade (TRG) score was significantly associated with DFS (hazard ratio (HR) 0·21, 95 per cent c.i. 0·07 to 0·70) and OS (HR 0·27, 0·13 to 0·59). Five-year DFS and OS rates related to TRG were 64 and 62 per cent respectively for 25 good responders versus 8·0 and 8·6 per cent for 127 poor responders ( P < 0·001). Conclusion: The prescription of NAC to all patients with OAC risks delay in effective treatment of patients who are relatively chemoresistant, given the variability in pathological response. Identification of patients with OAC who may derive the most benefit from NAC should be the focus. Graphical Abstract: Following propensity adjustment for stage, age and sex, neoadjuvant therapy was not associated with survival. Tumour regression is a powerful prognostic indicator, and future research should focus on identifying patients who will derive the most benefit from neoadjuvant chemotherapy. New approaches needed to identify non-responders to chemotherapy